A Perspectiva (Inter)dependentista de Fernando Henrique Cardoso: uma visão particular do desenvolvimento capitalista brasileiro - Traspadini, Roberta Sperandio (1998)
This study investigates the writings of Fernando Henrique Cardoso, current president of Brazil, who was an outstanding theorist of the Latin American development since the 1960s. The work seeks to confront the theoretical constructions of Cardoso from the 60s onwards, with the proposal and management current government agencies, whose intention is to make the Brazilian economy more competitive internationally. In order to understand the way in which the author positions himself and articulates its ideas with regard to Latin American economic development American and, mainly, Brazilian, we will stick to three main books, which are: The Brazilian industrial entrepreneur (1963), Dependence and development in Latin America (1967) and Ideas and their place (1980). We believe that they allow us to conclude whether the hypothesis we are working is correct or not. That is, we will investigate whether the current position of the president of the Republic Fernando Henrique Cardoso, with regard to the internationalization of economy as well as the restructuring of the State, is sustained, in a coherent in his academic writings dated from the 1960s.